Making Health Care Truly Affordable after Health Care Reform. Issue 4 (2016) - Jost, Timothy Stoltzfus; Pollack, Harold A.
Abstract : The Affordable Care Act (ACA) is an essential first step toward making health insurance more affordable for lower and moderate income Americans. It has accomplished historic reductions in the proportion of Americans who are uninsured. The number of Americans reporting delaying medical care for financial reasons has declined by approximately one-third since 2010. Medicaid expansions, in particular, have significantly reduced financial burdens and accompanying anxieties experienced by low-income Americans in states that have embraced this opportunity. Consistent with these finding, one recent analysis of credit report data finds that Medicaid expansion was associated with between a $600 and $1000 decline in collection balances among individuals who gained coverage. Notwithstanding these gains, premiums and cost-sharing are still too high for many Americans. And cost-sharing has continued to edge higher for the majority of Americans who have coverage through employer-based plans. Measures to address these challenges must build on the ACA to provide greater protection to millions of Americans and to address continued dissatisfaction with our health care financing system among middle-income Americans.